A 'new' hierarchy of English teachers: the 'half-native' English teacher as a neoliberal, racialized and gendered subject. Issue 1 (2nd January 2022) - Martinez, Julius C.
ABSTRACT: This article challenges binary-oriented approaches to understanding the issue of the native English-speaking teacher (NEST) and the non-native English-speaking teacher (NNEST). It unpacks a novel terminology called the 'half-native English-speaking teacher' (HNEST) that appears on the website of an online English school for Japanese students. The article also examines the privilege–marginalization experiences of three HNESTs. The analysis of the website shows that the multimodal representations tacitly generate a 'new' hierarchy of English teachers, with presupposed NEST, HNEST and NNEST categories arranged from top to bottom. While this hierarchy appears 'new' on the surface, it reinforces old and restricting discourses of idealization and essentialization. The analysis of the participants' interviews, meanwhile, suggests that privilege–marginalization is not uniformly and categorically experienced. This complex fluidity of privilege–marginalization is dynamically interwoven in broader discourses of neoliberalism, race and gender.